2019
DOI: 10.18006/2019.7(5).481.488
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Impact of Wastewater Irrigation in the Era of Global Concern of Antibiotic Resistance: A Perspective From a Developing Country

Abstract: Insufficient supply of fresh water remains a global problem, particularly in Africa and Middle East. Using wastewater effluent as an alternative water source for irrigating crops has become a feasible alternative; this relieves demand for fresh water. Wastewater treatment plants (WWTPs) are widely recognized as reservoirs for antibiotic resistant genes (ARGs) that are associated with pathogenesis. This is because WWTPs receive water from various sources and frequently contain antibiotic resistance determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Irrigation of crops using wastewater effluent has been adapted by many African countries such as South Africa, Tunisia, Zimbabwe and Botswana, this reduces the need for fresh water while improving food security ( Khalid et al., 2018 ; Onalenna and Rahube 2019 ). Increasing reports have shown that plants have the ability to passively uptake water soluble contaminants through the roots which can be translocated and concentrated into other parts of the plant such as leaves, although this more so in hydroponic cultures compared to conventional crops in soil ( Pullagurala et al., 2018 ; Madikizela et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation of crops using wastewater effluent has been adapted by many African countries such as South Africa, Tunisia, Zimbabwe and Botswana, this reduces the need for fresh water while improving food security ( Khalid et al., 2018 ; Onalenna and Rahube 2019 ). Increasing reports have shown that plants have the ability to passively uptake water soluble contaminants through the roots which can be translocated and concentrated into other parts of the plant such as leaves, although this more so in hydroponic cultures compared to conventional crops in soil ( Pullagurala et al., 2018 ; Madikizela et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%